Toxoplasma gondii, Suicidal Behavior, and Intermediate Phenotypes for Suicidal Behavior - Postolache, Teodor T.; Wadhawan, Abhishek; Rujescu, Dan; Hoisington, Andrew J.; Dagdag, Aline; Baca-Garcia, Enrique; Lowry, Christopher A.; Okusaga, Olaoluwa O.; Brenner, Lisa A. (Frontiers in Psychiatry, 2021)
Within the general literature on infections and suicidal behavior, studies on Toxoplasma gondii (T. gondii) occupy a central position. This is related to the parasite’s neurotropism, high prevalence of chronic infection, as well as specific and non-specific behavioral alterations in rodents that lead to increased risk taking, which are recapitulated in humans by T. gondii’s associations with suicidal behavior, as well as trait impulsivity and aggression, mental illness and traffic accidents. This paper is a detailed review of the associations between T. gondii serology and suicidal behavior, a field of study that started 15 years ago with our publication of associations between T. gondii IgG serology and suicidal behavior in persons with mood disorders. This legacy article presents, chronologically, our primary studies in individuals with mood disorders, schizophrenia in Germany, recent attempters in Sweden, and in a large cohort of mothers in Denmark. Then, it reviews findings from all three meta-analyses published to date, confirming our reported associations and overall consistent in effect size [ranging between 39% and 57% elevation of odds of suicide attempt in T. gondii immunoglobulin (IgG) positives]. Finally, the article introduces certain links between T. gondii and biomarkers previously associated with suicidal behavior (kynurenines, phenylalanine/tyrosine), intermediate phenotypes of suicidal behavior (impulsivity, aggression) and state-dependent suicide risk factors (hopelessness/dysphoria, sleep impairment). In sum, an abundance of evidence supports a positive link between suicide attempts (but not suicidal ideation) and T. gondii IgG (but not IgM) seropositivity and serointensity. Trait impulsivity and aggression, endophenotypes of suicidal behavior have also been positively associated with T. gondii seropositivity in both psychiatrically healthy as well as in patients with Intermittent Explosive Disorder. Yet, causality has not been demonstrated. Thus, randomized interventional studies are necessary to advance causal inferences and, if causality is confirmed, to provide hope that an etiological treatment for a distinct subgroup of individuals at an increased risk for suicide could emerge.